Serum miR-497-5p serves as a diagnostic biomarker for acute coronary syndrome and predicts the occurrence of major adverse cardiovascular events after percutaneous coronary intervention. Issue 4 (1st April 2022) - Chen, Tao; Zhang, Xueshan; Qian, Wei; Zhou, Ran; Su, Mingyu; Ma, Yanfeng
ABSTRACT: This study aimed to investigate the diagnostic value of microRNA (miR)-497-5p in acute coronary syndrome (ACS) and its predictive value for the occurrence of adverse major adverse cardiovascular events (MACEs). Real-time quantitative polymerase chain reaction (RT-qPCR) was performed to detect the expression of serum miR-497-5p in 110 ACS patients and 82 controls. And miR-497-5p levels were found to be significantly elevated in the patients (P < 0.001). Pearson correlation coefficient confirmed that miR-497-5p was positively correlated with Gensini scores (r = 0.684). The area under the Receiver-operating characteristic (ROC) curve was 0.861, which significantly identified patients with ACS, and was confirmed by logistic regression (OR = 8.533, 95%CI = 4.113–17.787, P < 0.001). Kaplan-Meier and Cox regression was performed to evaluate the predictive value of miR-497-5p in the occurrence of MACEs during a 6-month follow-up after percutaneous coronary intervention (PCI) in patients with ACS. The results demonstrated that miR-497-5p was an independent predictor of MACEs (HR = 4.773, 95%CI = 1.569–12.036, P = 0.013) and that patients with high level of miR-497-5p were more likely to develop MACEs after PCI (long-rank P = 0.019). Finally, miR-497-5p positively correlated with endothelial proinflammatory and adhesion factors. Our study suggests that serum miR-497-5p is a potential diagnostic marker for ACS and its elevated levels can predict a high risk of MACEs in ACS patients after PCI. And this may be associated with vascular endothelial injury. Graphical abstract: uf0001